Principles of Corporate Finance. - Brealey, Richard A; Myers, Stewart C; Allen, Franklin (New York : McGraw-Hill, 2017)
This new international edition provides increased coverage of the procedures for estimating the cost of capital, expanded coverage of risk management techniques and the use and misuse of derivatives, and additional coverage of agency problems.
Keywords: Corporations--Finance; Business enterprises -- Finance -- Management